MENINGKATKAN ANGKA BEBAS JENTIK MENGGUNAKAN OVITRAP DI UPT KESMAS SUKAWATI II KABUPATEN GIANYAR - Mochammad Choirul Hadi; I Nyoman Sujaya; I Nyoman Purna; I Wayan Jana (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
ABSTRACT. Ovitrap which has been widely known as a mosquito trap tool has not been widely used by the people of Bali. The introduction of ovitrap to the Batubulan Kangin Village community is the goal of community service activities in order to be able to use cheap, easy, and safe mosquito trap equipment, with the hope that it will be able to increase the rate of larval free. The method used by the Team is to provide counseling and provide training in making ovitraps and placing ovitraps inside and outside the home. The results of community service activities succeeded in increasing public knowledge about the benefits of ovitrap, how to make ovitrap, attractants and how to install it around their homes. The counseling and training activities held in the Batubulan Kangin Village Office Hall, Sukawati District, Gianyar regency attended by 52 people consisting of Puskesmas Staff, Jumantik, Village Health Cadres, and Hamlet Heads. Of the 9 Jumantik who took part in the outreach activities, immediately conducted socialization and invited 71 residents to use Ovitrap in their homes.Besides succeeding in changing the public's knowledge about mosquito eradication techniques, this service also succeeded in increasing the larva free rate from 54.9% to 95.8%.Keywords: ovitrap, attractant, larva free number